A Comparison of Two Structurally Related Human Milk Oligosaccharide Conjugates in a Model of Diet-Induced Obesity - Ramadhin, Jessica; Silva-Moraes, Vanessa; Nagy, Tamas; Norberg, Thomas; Harn, Donald (Frontiers in Immunology, 2021)
Obesity is the largest risk factor for the development of chronic diseases in industrialized countries. Excessive fat accumulation triggers a state of chronic low-grade inflammation to the detriment of numerous organs. To address this problem, our lab has been examining the anti-inflammatory mechanisms of two human milk oligosaccharides (HMOs), lacto-N-fucopentaose III (LNFPIII) and lacto-N-neotetraose (LNnT). LNFPIII and LNnT are HMOs that differ in structure via presence/absence of an α1,3-linked fucose. We utilize LNFPIII and LNnT in conjugate form, where 10-12 molecules of LNFPIII or LNnT are conjugated to a 40 kDa dextran carrier (P3DEX/NTDEX). Previous studies from our lab have shown that LNFPIII conjugates are anti-inflammatory, act on multiple cell types, and are therapeutic in a wide range of murine inflammatory disease models. The α1,3-linked fucose residue on LNFPIII makes it difficult and more expensive to synthesize. Therefore, we asked if LNnT conjugates induced similar therapeutic effects to LNFPIII. Herein, we compare the therapeutic effects of P3DEX and NTDEX in a model of diet-induced obesity (DIO). Male C57BL/6 mice were placed on a high-fat diet for six weeks and then injected twice per week for eight weeks with 25µg of 40 kDa dextran (DEX; vehicle control), P3DEX, or NTDEX. We found that treatment with P3DEX, but not NTDEX, led to reductions in body weight, adipose tissue (AT) weights, and fasting blood glucose levels. Mice treated with P3DEX also demonstrated improvements in glucose homeostasis and insulin tolerance. Treatment with P3DEX or NTDEX also induced different profiles of serum chemokines, cytokines, adipokines, and incretin hormones, with P3DEX notably reducing circulating levels of leptin and resistin. P3DEX also reduced WAT inflammation and hepatic lipid accumulation, whereas NTDEX seemed to worsen these parameters. These results suggest that the small structural difference between P3DEX and NTDEX has significant effects on the conjugates’ therapeutic abilities. Future work will focus on identifying the receptors for these conjugates and delineating the mechanisms by which P3DEX and NTDEX exert their effects.